Skier and snowboarder speeds at US ski areas - Lenka L. Stepan; Irving S. Scher; Gerhard Ruedl; Jasper E. Shealy (JSAMS Plus, 2023)
Objectives: To determine typical speeds of skiers and snowboarders on-piste groomed trails across the United States (US). Design and methods: On-slope speeds of skiers and snowboarders were measured on trails of varying difficulty at 8 ski areas across the US. The trail difficulty designation and slope were documented for each location where speed measurements were taken. The equipment used (skis or snowboard), whether a helmet was worn, and the estimated ability (determined by the researchers) of snowsports participants were recorded. A multiple linear regression analysis was performed to determine the influence of these individual and environmental factors on the speeds of snowsports participants. Results: 4164 speed observations were made between 2004 and 2020 on groomed trails at 8 ski areas representing 5 geographic regions in the United States. Across all observations, the average speed was 34.9 ​± ​13.6 ​km/h. The ability of the snowsports participant had the largest effect on speed. Advanced snowsports participants traveled faster (44.5 ​± ​11.7 ​km/h) than intermediates (32.4 ​± ​9.9) and beginners (19.9 ​± ​7.2). Skiers on average were faster (35.8 ​± ​13.8 ​km/h) than snowboarders (33.0 ​± ​13.2 ​km/h) and beginner and intermediate snowboarders were slower on average than their skiing counterparts. While the average speeds increased with increasing trail difficulty and slope, the correlation was weak (R2 ​= ​0.15). Conclusions: The ability of the snowsports participant was found to be the most influential factor affecting speed.